2020
DOI: 10.1016/j.omtn.2019.11.025
|View full text |Cite
|
Sign up to set email alerts
|

H19 Increases IL-17A/IL-23 Releases via Regulating VDR by Interacting with miR675-5p/miR22-5p in Ankylosing Spondylitis

Abstract: Long non-coding RNA (lncRNA) H19 is associated with inflammatory diseases, but the molecular mechanism of H19 in the inflammatory process of ankylosing spondylitis (AS) is unclear. Here, we investigated the role of H19 and its downstream molecules in the inflammation of AS by microarray analysis, qRT-PCR, western blot, and dual-luciferase reporter assay. H19 small interfering RNA (siRNA) (Si-H19) and adenovirus (AD-H19) were used to decrease and increase H19 expression, respectively. 42 annotated lncRNAs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 55 publications
(115 reference statements)
0
33
0
Order By: Relevance
“…The first is that we found that ESR2 was also upregulated by miR22-5p, but it was not through the regulation of promoter region methylation of ESR2; hence, the regulatory mechanisms are needed to be further studied. In addition, some studies have revealed the functions of miR22-5p in other diseases [32,33]. However, this study only focused on that miR22-5p dysregulates directly the expression of TET2 in the eutopic endometrium of endometriosis without the exploration of specific functions of miR22-5p.…”
Section: Plos Onementioning
confidence: 99%
“…The first is that we found that ESR2 was also upregulated by miR22-5p, but it was not through the regulation of promoter region methylation of ESR2; hence, the regulatory mechanisms are needed to be further studied. In addition, some studies have revealed the functions of miR22-5p in other diseases [32,33]. However, this study only focused on that miR22-5p dysregulates directly the expression of TET2 in the eutopic endometrium of endometriosis without the exploration of specific functions of miR22-5p.…”
Section: Plos Onementioning
confidence: 99%
“…Many studies indicate that lncRNA H19 is involved in the pathogenesis of several human tumors [33][34][35]. H19 also plays a specific regulatory role in diabetic retinopathy, atherosclerosis, and ankylosing spondylitis [36][37][38]. H19 levels are significantly higher in ICH rat models than in normal rats [21].…”
Section: Discussionmentioning
confidence: 99%
“…H19 also plays a pivotal role in diverse in ammations. In rheumatoid arthritis, H19 promoted the in ammation by degradation of miR-103a [50]; in ankylosing spondylitis, H19 interacts with miR-675-5p and miR-22-5p to increase IL-17A/IL-23 release [51]; H19 also regulates ageing and age-related diseases by interplay with in ammation [52]. H19 also contributes to the genesis and metastasis of different type of cancers by reexpression in cancer tissues, e. g., hepatocellular carcinoma [53], thyroid cancer cells [54], non-small cell lung cancer [55], etc.…”
Section: Discussionmentioning
confidence: 99%